Let’s Talk About BiTEs and Other Drugs in the Real-Life Setting for B-Cell Acute Lymphoblastic Leukemia - Deak, Dalma; Pop, Cristina; Zimta, Alina-Andreea; Jurj, Ancuta; Ghiaur, Alexandra; Pasca, Sergiu; Teodorescu, Patric; Dascalescu, Angela; Antohe, Ion; Ionescu, Bogdan; Constantinescu, Catalin; Onaciu, Anca; et al. (Frontiers in Immunology, 2019)
Background: Therapy for acute lymphoblastic leukemia (ALL) are currently initially efficient, but even if a high percentage of patients have an initial complete remission (CR), most of them relapse. Recent data shows that immunotherapy with either bispecific T-cell engagers (BiTEs) of chimeric antigen receptor (CAR) T cells can eliminate residual chemotherapy-resistant B-ALL cells. Objective: The objective of the manuscript is to present improvements in the clinical outcome for chemotherapy-resistant ALL in the real-life setting, by describing Romania's experience with bispecific antibodies for B-cell ALL. Methods: We present the role of novel therapies for relapsed B-cell ALL, including the drugs under investigation in phase I-III clinical trials, as a potential bridge to transplant. Blinatumomab is presented in a critical review, presenting both the advantages of this drug, as well as its limitations. Results: Bispecific antibodies are discussed, describing the clinical trials that resulted in its approval by the FDA and EMA. The real-life setting for relapsed B-cell ALL is described and we present the patients treated with blinatumomab in Romania. Conclusion: In the current manuscript, we present blinatumomab as a therapeutic alternative in the bridge-to-transplant setting for refractory or relapsed ALL, to gain a better understanding of the available therapies and evidence-based data for these patients in 2019.